(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This study is devoted to the problem of organizing the main terms in the restoration of archaeological ceramics and bringing them to an unambiguous interpretation. The importance of semantic filling of the basic concepts in archaeology, museology and restoration, such as trait, type, kind, property, quality, function is analyzed. This allowed to identify their differences and similarities. The difference in understanding is due to the objectives of each of the related disciplines. The significance of the raised topic lies in the fact that in the preservation of archaeological cultural heritage it is extremely important to finally resolve the issues related to the translation of theoretical provisions into criteria and guidelines for concrete restoration work. This is connected with the necessity to 1. define the ultimate goal of restoration - what should be restored in the end - the appearance, properties, quality, functions of the monument or to eliminate signs of its destruction, as well as 2. to evaluate the quality of the work performed. Today, in the absence of a clearly formulated conceptual apparatus, unsuccessful restoration often leads to irreversible consequences and sometimes to the death of monuments. Based on many years of work with museum collections, in archaeological expeditions and pedagogical experience, the author has made an attempt to bring the existing terminology to an unambiguous understanding. He does not claim to solve all the above problems, as they need discourse, but considers it necessary to bring them up for discussion.